Impact of vaccination on the presence and severity of symptoms in hospitalized patients with an infection of the Omicron variant (B.1.1.529) of the SARS-CoV-2 (subvariant BA.1). (May 2023) - Beraud, Guillaume; Bouetard, Laura; Civljak, Rok; Michon, Jocelyn; Tulek, Necla; Lejeune, Sophie; Millot, Romain; Garchet-Beaudron, Aurélie; Lefebvre, Maeva; Velikov, Petar; Festou, Benjamin; Abgrall, Sophie; et al.
Abstract: Objectives: The emergence of SARS-CoV-2 variants raised questions about the extent to which vaccines designed in 2020 have remained effective. We aimed to assess whether vaccine status was associated with the severity of Omicron SARS-CoV-2 infection in hospitalized patients. Methods: We conducted an international, multi-centric, retrospective study in 14 centres (Bulgaria, Croatia, France, and Turkey). We collected data on patients hospitalized for ≥24 hours between 1 December 2021 and 3 March 2022 with PCR-confirmed infection at a time of exclusive Omicron circulation and hospitalization related or not related to the infection. Patients who had received prophylaxis by monoclonal antibodies were excluded. Patients were considered fully vaccinated if they had received at least two injections of either mRNA and/or ChAdOx1-S or one injection of Ad26.CoV2-S vaccines. Results: Among 1215 patients (median age, 73.0 years; interquartile range, 57.0–84.0; 51.3% men), 746 (61.4%) were fully vaccinated. In multivariate analysis, being vaccinated was associated with lower 28-day mortality (Odds Ratio [95% Confidence Interval] (OR [95CI]) = 0.50 [0.32–0.77]), intensive care unit admission (OR [95CI] = 0.40 [0.26–0.62]), and oxygen requirement (OR [95CI] = 0.34 [0.25–0.46]), independent of age and comorbidities. When co-analysing these patients with Omicron infection with 948 patients with Delta infection from a study we recently conducted, Omicron infection was associated with lower 28-day mortality (OR [95CI] = 0.53 [0.37–0.76]), intensive care unit admission (OR [95CI] = 0.19 [0.12–0.28]), and oxygen requirements (OR [95CI] = 0.50 [0.38–0.67]), independent of age, comorbidities, and vaccination status. Discussion: Originally designed vaccines have remained effective on the severity of Omicron SARS-CoV-2 infection. Omicron is associated with a lower risk of severe forms, independent of vaccination and patient characteristics.